Supporting the Use of Flipbook Learning Source (FLS) in the Merdeka Curriculum to Provide Quality Teaching Materials - Wicaksono, Iwan; Sutarto, Sutarto; Hariyadi, Slamet; Indrawati, Indrawati (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
The Merdeka Curriculum is a diverse intra-curricular learning framework that maximizes content to allow learners ample time to understand concepts and strengthen competencies. This curriculum demands independence and creativity in teaching and learning, necessitating engaging and effective educational media. The FLS offers innovative solutions for creating interactive and engaging digital teaching materials. This study aims to assist teachers at Ma'arif Perintis 04 Senior High School in Tempurejo Village, Jember, in utilizing and implementing FLS to develop quality teaching materials in the era of the Merdeka Curriculum. The training activity approach is Participatory Rural Appraisal. With FLS, the learning process is expected to become more engaging, interactive, and effective, enhancing student interest and learning outcomes. The research methodology included identifying the needs and challenges faced by teachers in preparing teaching materials, training in flipbook creation using specific software, intensive mentoring in digital teaching material development, and evaluating and providing feedback on the created materials. The results indicated improved teachers' competencies in creating digital teaching materials using FLS. Teachers were able to produce appealing flipbooks that aligned with the Merdeka Curriculum standards. Moreover, using flipbooks in learning has increased student participation and motivation. Evaluations were conducted through observation, interviews, and questionnaires to assess the effectiveness of the training and the implementation of FLS in teaching. The findings show that this mentorship successfully improved the quality of the teaching materials. The hope for the future is that teachers can be more creative and innovative in creating learning in the classroom. Top of Form